Towards understanding nuclear pore complex architecture and dynamics in the age of integrative structural analysis - Hurt, Ed; Beck, Martin (Current opinion in cell biology, 2015)
Determining the functional architecture of the nuclear pore complex, that remains only partially understood, requires bridging across different length scales. Recent technological advances in quantitative and cross-linking mass spectrometry, super-resolution fluorescence microscopy and electron microscopy have enormously accelerated the integration of different types of data into coherent structural models. Moreover, high-resolution structural analysis of nucleoporins and their in vitro reconstitution into complexes is now facilitated by the use of thermostable orthologs. In this review we highlight how the application of such technologies has led to novel insights into nuclear pore architecture and to a paradigm shift. Today nuclear pores are not anymore seen as static facilitators of nucleocytoplasmic transport but ensembles of multiple overlaying functional states that are involved in various cellular processes.